Temperature and ph control of dark fermentation bioreactor to produce biohydrogen from palm oil mill effluent by using fuzzy logic controlleri - Ikhmal Zariq Al Imran Jamal Ikhsan; Norliza Abd Rahman; Jarinah Mohd Ali (Penerbit Universiti Kebangsaan Malaysia, 2023)
THydrogen is the main choice of renewable fuel since it brings significant benefits compared with the other conventional fuels, such as the use of waste substrate, cleaner and highest energy density. Biological hydrogen production route is cost efficient since it can be processed in ambient conditions, easy operational techniques while keeping the environment safe. Dark fermentation to produce bio-hydrogen has received widespread attention from researchers in the present decades especially due to not requires light sources. This work is a study of the optimization of process conditions particularly pH and temperature of a dark fermentation bioreactor to produce Bio-H2 from palm oil mill effluent (POME) by using fuzzy logic controller. The simulation started by developing process and instrumentation diagram (P&ID) of bioreactor. Then a conventional PID controller and fuzzy logic controller were simulated by using MATLAB SIMULINK and the results were compared with each other in terms of safety aspect. The temperature of 37oC and pH of 6 is the optimum conditions that needs to be maintained to yield the hydrogen at 2.79 mol H2 mol-1 glucose. The pH is able to reach optimum value at 600s and 30s by using the PID controller and fuzzy logic controller, respectively. Same goes to temperature control, where the parameter reaches optimum value at 200s and 0.3s respectively. Based on these promising results, fuzzy logic controller is a good replacement for the conventional control systems since it requires shorter time to optimize process conditions, consequently making sure the safety aspect is well guaranteed.